Pathogenesis and Diagnostic Significance of EBV-miR-BARTs in Nasopharyngeal Carcinoma. (3rd October 2022) - Wu, Zhen; Zhang, Xiaoling; Liu, Pinjing; Wei, Aiyou; Ouyang, Wei; Xiao, Shengjun
Abstract : Objective . Examining the role of EBV-miR-BARTs in nasopharyngeal cancer etiology and diagnosis. Method . As the subjects of this study, nasopharyngeal cancer cell lines were chosen and then randomly assigned to one of four groups: the control group, EBV-miR-BART5-3p NC, EBV-miR-BART5-3p mimics, and EBV-miR-BART5-3p inhibitor groups. Utilizing reverse transcription polymerase chain reaction, we determined the levels of gene expression in nasopharyngeal cancer cells that had been treated with EBV-miR-BART5-3p (RT-PCR). The MTT, Transwell, and scratch tests were used to determine the degree to which cells underwent apoptosis, invasion, and migration. The Western blotting method was used in order to examine the protein expression. Result . Compared with normal nasopharyngeal cells, P   0.05 showed that nasopharyngeal cancer cells had greater EBV-miR-BART5-3p expressions and proliferation rates in the control, EBV-miR-BART5-3p NC, and EBV-miR-BART5-3p No statistically significant differences were seen between the mimic groups (P > 0.05 ); compared with the control group, the proliferation rate of the EBV-miR-BART5-3p inhibitor group was lower with P < 0.05 . At a significance threshold of P   0.05, there was no difference in the rates of apoptosis between the control group and the EBV-miR- BART5-3p NC group. Comparing the control group to the EBV-miR-BART5-3p mimics group and the EBV-miR-BART5-3p inhibitors group revealed that the rate of apoptosis was dramatically enhanced in the EBV-miR-BART5-3p inhibitors group but significantly decreased in the control group (P   0.05 ). When comparing the control group to the EBV-miR-BART5-3p NC group, there was no statistically significant change in the total number of invasive cells (P > 0.05 ). When comparing the EBV-miR-BART5-3p mimics group to the control group, we found a statistically significant increase in the former and a decrease in the latter (P   0.05 ). The migration rates of the control group, the EBV-miR-BART5-3p NC group, and the EBV-miR-BART5-3p mimics group did not vary from one another in a way that was statistically significant (P > 0.05 ). When compared to the control group, the migration rate was considerably (P 0.05) lower in the EBV-miR-BART5-3p inhibitor group. There were no discernible changes identified (P > 0.05 ) in the levels of Bcl-2 protein expression in the control group, the EBV-miR-BART5-3p NC group, and the EBV-miR-BART5-3p mimic group in a research that compared these three groups. Protein levels of BCL-2 were significantly decreased (P   0.05 ) in the EBV-miR-BART5-3p inhibitor group, in comparison to the control group. When comparing the control and EBV- miR-BART5-3p NC groups, we found no statistically significant differences in Bax and Caspase-3 protein expression levels (P > 0.05 ). The protein expressions of Bax and Caspase-3 were statistically significantly greater in the EBV-miR-BART5-3p contrast between the inhibitor and control groups. When comparing the protein expressions of MMP-2 and MMP-9 between the control group, the EBV-miR-BART5-3p NC group, and the EBV-miR-BART5-3p mimics group, there was no statistically significant change (P > 0.05 ). Protein levels of MMP-2 and MMP-9 were inhibited by EBV-miR-BART5-3p to a greater extent (P   0.05 ) in the experimental group compared to the control group. Conclusion . The understanding that inhibiting expression of EBV-miR-BART5-3p might reduce the risk of developing nasopharyngeal cancer may help direct clinical treatment for the condition.